Comparative and systematically analysis of the effects of single and high-entropy rare earth oxide additives on the some physical properties and radiation shielding properties of copper composites - Kanca, Muhammed Sait; Yilmaz, Demet; Tasgin, Yahya; Kok, Mediha; Guler, Seval Hale (Elsevier Science Sa, 2026)
In this study, the effects of rare earth oxides (Gd2O3, La2O3, Eu2O3, Pr2O3, Dy2O3, and Y2O3) and high-entropy oxide (GdLaEuPrDyY)2O3 additives on the structural, mechanical, and radiation shielding properties of copper matrix composites were investigated. XRD and SEM-EDS analyses showed that the high-entropy oxide successfully formed in a single-phase bixbyite structure after mechanical alloying and was homogeneously distributed within the copper matrix. The rare earth oxide additive significantly reduced the crystal grain size of the Cu matrix and improved its mechanical properties. Specifically, the microhardness value reached 68.3 Hv in the composite with 20% high-entropy oxide additive, representing an increase of approximately 111% compared to pure copper (32.3 Hv). Gamma shielding results showed that the rare earth oxide additive significantly increased the photon attenuation capacity. Specifically, at 242 keV energy, the Dy2O3 additive increased the MAC value from 0.141 cm2/g to 0.246 cm2/g, providing a 74.5% improvement. The most important result is that the composite with 20% high-entropy oxide additive showed the highest shielding performance, achieving a MAC value of 0.278 cm2/g, which is significantly superior to pure copper. Furthermore, this composite exhibited the lowest HVL and MFP values, demonstrating the highest photon shielding efficiency. Neutron shielding analyses revealed that Gd2O3 and high-entropy oxide additives, in particular, increased thermal neutron attenuation performance to approximately 100%. These results demonstrate that high-entropy oxide additives provide a stronger impact compared to single oxide additives, offering superior performance in both gamma and neutron shielding. Consequently, copper composites doped with (GdLaEuPrDyY)2O3 stand out as promising alternative shielding materials for nuclear facilities, radiation protection systems, and advanced engineering applications due to their high shielding efficiency, improved mechanical properties, and non-toxic composition.
Keywords: Copper matrix composites; Rare-earth oxides; High-entropy oxide (HEO); Gamma attenuation; Neutron shielding; Mechanical alloying